Investigation of the current Innovative Industrialized Building Systems (IBS) in Malaysia - Al-Aidrous, A.-H.M.H. (Institute of Electrical and Electronics Engineers Inc., 2021)
Adopting sustainable and innovative building materials is becoming an ever-increasing necessity to reduce the impact of construction development on material resources consumption and climate change. Prefabricated construction has received an immense research attention recently, with precast concrete as the main prefabricated technique explored. However, there is a limited attention for innovative and composite materials and systems. Therefore, this research aims to investigate the recent development of innovative Industrialized Building Systems (IBS) in Malaysia. Literature review based on recent journal articles, government technical reports, companies' reports, and news articles were used in this study. The result of this investigation revealed that there has been a sharp increase in innovative system manufacturers from around 10 companies in 2010 up to 70 companies in 2020. This is primarily due to the advantages reported on innovative systems compared to bulky precast systems including design flexibility, efficient thermal performance, and green materials. This study provides better guidance for practitioners to better understand the innovative systems potential, leading to higher acceptance and greater use of the systems. Â© 2021 IEEE.